Uprava - Boštjančič, Eva (Uprava (Ljubljana), 2010)
Our scope of interest in this article is employed women in Slovenia working in public sector (state administration, education and healthcare) and in economy. Working women's verious roles today may lead to conflict or enrichment. This study seeks to determine the connection between their multiple roles, life orientation, and life satisfaction. The study was carried out through internet questionnaires and surveyed 1298 working women. Their average age was 35,6 years. A total of 43% participants had at least college degree. The results show that working women are at least satisfied with their leisure time and most satisfied with their maternal role. The most satisfied women work in pharmaceuticals and healthcare, and the least satisfied work in the state administration sector. Women with multiple roles are more satisfied with their maternal role but less satisfied with their partners and leisure time. They are also more optimistic.
Keywords: družina; family; javni sektor; materinstvo; poklicni razvoj; public sector; raziskave; Slovenia; Slovenija; uspešnost; woman; zadovoljstvo; zasebni sektor; ženske